The Indian Bidi Industry: Trends in Employment and Wage Differentials - Arora, Monika; Datta, Pritam; Barman, Avnika; Sinha, Praveen; Munish, Vineet Gill; Bahl, Deepika; Bhaumik, Soumyadeep; Nazar, Gaurang P.; Tullu, Fikru (Frontiers in Public Health, 2020)
Background The bidi industry in India is predominantly an unorganized sector. It continues to enjoy tax benefits, arguably, to protect bidi workers’ interests and employment. Our objective was to study trends in employment and wage differentials in the bidi industry using nationally representative data. Methods We studied trends in employment and wages in the bidi industry using secondary data from the National Sample Survey Office (NSSO) and the Central Statistics Office (CSO), Government of India - the Annual Survey of Industries (ASI) (2000-01 to 2011-12) and Enterprises Survey (2000-01, 2005-06, 2010-11) Results The bidi industry contributed to only 0.65% of the total gross value added (GVA) by the entire manufacturing industry. Employment in this industry was primarily through contractors. Bidi workers earned only 17% of wages compared to workers in other manufacturing industries. Although females constituted the majority of bidi workers, they earned INR 7000 to 8000 (USD 155.7 to 178) less than male bidi workers annually. Despite the increase in bidi industry profits from INR 1.7 billion (USD 37.8 million) in 2005-06 to INR 12.8 billion (USD 285 million) in 2010-11, the wages of bidi workers have continued to decline over this period. Conclusion Bidi workers earn much less compared to workers in other manufacturing industries and are subject to income inequality. There is a need to increase registration of the bidi industry for better administration of taxes and prevention of exploitation of the bidi workers. Skill building and alternative employment could provide better job quality, wages, social security and employment benefits.